Immuno-hematological consequence of intravenous drug abuse? - Jindal, Aikaj (Asian J Transfus Sci, 2020)
Intravenous (IV) drug abuse has been well established to be the source of transfer of infections, such as HIV, hepatitis C virus, and hepatitis B virus. However, often overlooked fact is that IV drug abusers have a potential for developing alloimmunization due to universal practice of flushing/washing out the syringe by own blood to rinse out the drug in the syringe. We present here a case of a 28-year-old man who presented with a rather unique predicament of having developed four different alloantibodies after exposure to allogenic blood through IV drug abuse. This case was detected promptly due to routine usage of type and screen policy for all the patients receiving transfusion. Such screening for atypical antibodies must be instituted to preemptively identify these antibodies and arrange compatible blood, which could have been difficult otherwise, at short notice during routine crossmatch. This is the first of its kind case ever reported from India and has no precedence.